An overview of blockchain efficient interaction technologies - Liu, Feng; He, Sihao; Li, Zhenghao; Li, Zhibin (Frontiers in Blockchain, 2023)
The successful operation of Bitcoin has made its underlying blockchain technology receive wide attention. As the application scenarios of blockchain technology are enriched, the requirements for its performance are getting higher. Therefore, it is of utmost importance to effectively solve the problem of high-performance data interaction in the blockchain. In this paper, based on relevant domestic and foreign research literature, we start from the development history of blockchain technology and review the relevant research work on improving the performance of blockchain from three perspectives: on-chain interaction technology, off-chain interaction technology, and cross-chain interaction technology in turn. The on-chain and off-chain interaction technologies improve performance by improving the architecture of the blockchain system. The performance improvement solution of on-chain interaction technology is to modify and optimize the basic protocol and architecture of the blockchain itself to achieve a performance improvement. Still, the impact of this approach is limited in terms of performance improvement. The performance improvement solution of off-chain interaction technology is to transfer part of the data processing to off-chain and only return the final result to on-chain for storage and recording, which reduces the burden of on-chain operation and improves the efficiency of data processing. In terms of cross-chain interaction technology, this paper analyses four mainstream technology, namely Notary Scheme, Side chain and Chain relay, Hash-Locking, and Distributed Private Key Control, and ultimately concludes through comparative analysis that cross-chain technology has a significant impact on improving blockchain performance. Finally, the paper provides a systematic overview of the above and an outlook on the possible future development of technologies related to enhancing blockchain performance.